Report on an experience of in-service teacher training on human rights and citizenship education - Ramos, Fernando Sadio (2011)
The text below presents a training experience on Human Rights and Citizenship Education which took place at three In-Service Teacher Training Courses. This experience occurred in the more general context of an ongoing Human Rights and Citizenship Education project, overseen by our institution, the College of Education – Polytechnic Institute of Coimbra, University of Granada and the Council of Europe (particularly, the European Youth Centre Budapest). In-service teacher training is an important component of this project, which seeks excellence and high-quality in both teaching and training. The use of non-formal education methodologies is a distinctive feature of this experience and of the project.